Blurring the Boundaries of Vision: Novel Functions of Intrinsically Photosensitive Retinal Ganglion Cells. (January 2013) - Matynia, Anna
Mammalian vision consists of the classic image-forming pathway involving rod and cone photoreceptors interacting through a neural network within the retina before sending signals to the brain, and a non image-forming pathway that uses a photosensitive cell employing an alternative and evolutionary ancient phototransduction system and a direct connection to various centers in the brain. Intrinsically photosensitive retinal ganglion cells (ipRGCs) contain the photopigment melanopsin, which is independently capable of photon detection while also receiving synaptic input from rod and cone photoreceptors via bipolar cells. These cells are the retinal sentry for subconscious visual processing that controls circadian photoentrainment and the pupillary light reflex. Classified as irradiance detectors, recent investigations have led to expanding roles for this specific cell type and its own neural pathways, some of which are blurring the boundaries between image-forming and non image-forming visual processes.